A Metal Bed Production Monitoring System using Internet of Things - Idrus, Muhamad Ridzuan; Tasiransurini Ab Rahman, (Evolution in Electrical and Electronic Engineering, 2023)
As the human population grows, the demand for essential goods, including metal beds is increasing day by day. This scenario benefits the bed manufacturing industry. However, the ratio of supply and demand is unbalanced due to inaccurate data on the quantity of production. Therefore, A Metal Bed Production Monitoring System using Internet of Things (IoT) was developed to overcome this problem. The implementation of this work uses an ESP32-type microcontroller module to develop a prototype of a metal bed production monitoring system for the manufacturing industry. The input received from the production line will be detected by the infrared sensor placed on the metal bed frame mold. This work provides a visual dashboard a production line information archived by using the Node-Red platform. The collected data is converted to .excel form which allows the management to monitor the quantity of production.